REFORMASI BIROKRASI PADA PEMERINTAH PROVINSI JAWA BARAT - Rohmadin, Sulthon (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2018)
AbstrAct Indonesia’s bureaucratic condition in the current reform era has not shown a good development direction, because there are still many unprofessional bureaucrats, acting as rulers, running corruption, collusion and nepotism (KKN) practices at the central, provincial and district levels. In addition, bureaucrats tend to choose comfort zones without competition, but rather based on seniority. Bureaucrats are generally not ready to enter the competitive zone.To transform a reliable and professional bureaucracy, the Government has formulated strategic policies. One of them is the Perpres No. 81/2010 on the Grand Design of Indonesian Bureaucracy 2010-2025, which is followed up by the PermenPAN RB No. 37 of 2013 on Guidelines for Formulating the Local Government Bureaucratic Reform Roadmap.The method used in this study is tailor made method combined with FGD (expert meeting) method with related bureaucratic apparatus, and Delphi technique, which is one of the techniques for involving stakeholders in decision making/policy by gathering opinions through questionnaires/questionnaire.This study resulted in 8 recommendations of the Bureaucratic Reform policy program in West Java which are expected to be able to encourage the establishment of a clean and good West Java Provincial government with adaptive characteristics, integrity, professionalism, high performance, freedom, and clean from corruption, collusion and nepotism (KKN) able to serve the public, be neutral, prosperous, dedicated and uphold the basic values and code of ethics of the apparatus. And of course it is able to realize the vision and mission of West Java Province that touches the interests of the wider community towards “West Java Forward and Prosperous” Keywords: bureaucratic reform, public service